METHODOLOGY OF TEACHING PHYSICS IN SCHOOLS - Xudoyberdiyeva Yulduz Xayrullo qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the features of the organization of the process of teaching physics in secondary school. The advantages of using new pedagogical technologies, a complex of electronic means for educational purposes are reflected. An example of educational technology for teaching physics is given.